Conflicts and consequences of single set of tax compliant transfer pricing - Mansikkamäki, Maiju (My University, 2021)
As the magnitude of the international trade increases, so does the importance of the pricing of the internal transactions, in other words, the importance of transfer pricing. Transfer prices determine how profits are allocated between related parties and thus, between coun-tries. Transfer pricing is an important tax concern, but it is also a management issue. Trans-fer pricing affects performance measurement and reward, which in turn influence the per-ceived fairness by managers. Transfer pricing also affects economic decision making in the companies and thus, the overall corporate performance. Transfer pricing has been noted to cause conflicts in organizations due to the diverging interest and interdependencies between buying and selling divisions. Top management also has its interests in the transfer pricing. Many organizations have adopted single set of transfer prices, meaning that the same transfer prices are used both for management control and tax purposes. The purpose of this study is to investigate what kind of tensions tax compliant single set of transfer pricing may cause in a decentralized organization, do the tensions benefit or harm the organization, and how they can be tackled. The study is carried out as a single case study, concentrating on one organization. The results reinforce the prior literature’s notion of the prevalence of transfer pricing tensions. Tax compliance might work as a limiting factor for transfer pricing, make the prices more rigid and aid centralization. These factors might increase the tensions experi-enced by reducing divisional autonomy and decreasing understanding over transfer pricing. Internal fighting over transfer pricing is a harm that consumes resources without adding value. Due to the important tax aspects the internal fighting receives potentially more at-tention and ties more management time. Transfer pricing tensions can generate information and facilitate management control, as identified in prior literature. In transfer pricing, many basic principles from tax perspective are very similar to the management perspective. Hence, facilitation of management control can simultaneously support tax compliance and control. Negotiated transfer prices are sometimes suggested as a resolution mechanism for transfer pricing conflict. However, they have practical challenges from tax perspective, so administrative processes might be more usable conflict resolution mechanism for tax com-pliant organizations.

Kansainvälisen kaupan kasvaessa konsernien sisäisen hinnoittelun eli siirtohinnoittelun merkitys korostuu. Siirtohinnat vaikuttavat siihen, miten voitot jakautuvat konserniin kuu-luvien yritysten kesken ja siten verotettavan tulon jakautumiseen eri maiden välillä. Tämän vuoksi siirtohinnoittelu on merkittävä kansainvälinen verokysymys. Siirtohinnoittelu on lisäksi tärkeä johdon ohjauksen kannalta. Siirtohinnoittelu vaikuttaa suorituksen mittauk-seen ja palkitsemiseen, joka taas vaikuttaa koettuun reiluuteen. Siirtohinnoittelu vaikuttaa myös organisaatioiden päätöksentekoon ja siten koko suorituskykyyn. Siirtohinnoittelun on tunnistettu aiheuttavan konflikteja ja jännitteitä organisaatioissa. Ostavalla ja myyvällä osapuolella on vastakkaiset tavoitteet ja ne ovat riippuvaisia toisis-taan, mikä on asetelmana altis konflikteille. Lisäksi konsernin keskusjohdolla on omat ta-voitteensa. Monet konsernit ovat ottaneet käyttöön yhden siirtohinnoittelujärjestelmän, jossa sa-moja siirtohintoja käytetään sekä verotarkoitukseen että johdon ohjaukseen. Tutkielma pyr-kii selvittämään, mitkä tekijät aiheuttavat siirtohinnoittelujännitteitä konserneissa, kun käytössä on vain yksi siirtohinnoittelujärjestelmä. Lisäksi tutkitaan, voiko havaituista jän-nitteistä olla haittaa tai hyötyä organisaatioille, ja miten jännitteitä voidaan hallita. Tutki-mus toteutettiin laadullisena tapaustutkimuksena tutkimalla yhtä konsernia. Tulokset vahvistavat aiemman kirjallisuuden käsityksen siirtohinnoittelukonfliktien yleisyydestä. Verovaikutus saattaa toimia rajoittavana tekijänä siirtohinnoittelussa, jäykistää siirtohintoja ja lisäksi johtaa siirtohinnoittelun keskittymiseen konsernin keskushallinnolle. Nämä tekijät saattavat lisätä jännitteiden määrää rajoittamalla yksiköiden autonomiaa ja vähentämällä ymmärrystä siirtohinnoista. Lisäksi veronäkökulman tärkeydellä saatetaan perustella jatkuvaa kiistelyä siirtohinnoista. Kiistelyn kuluttamat voimavarat ovat siirtohin-noittelujännitteiden aiheuttama haitta. Toisaalta jännitteet saattavat tuottaa tietoa ja tukea ohjausta. Siirtohinnoittelussa lähtökohdat johdon ohjauksen ja verotuksen näkökulmasta ovat lähellä toisiaan, joten johdon ohjauksen kontrolli voi samalla tukea myös verosääntö-jen toteutumisen seurantaa. Aiemmat tutkimukset suosivat neuvotteluja jännitteiden rat-kaisemiseksi. Neuvotellut siirtohinnat ovat haastavia perustella veroviranomaisille, joten hallinnolliset prosessit voivat osoittautua toimivammaksi menetelmäksi hallita jännitteitä.
Keywords: Siirtohinnoittelu, jännitteet, Transfer pricing, conflict